Isolated copper–tin atomic interfaces tuning electrocatalytic CO2 conversion - Wenhao Ren (Nature Portfolio, 2021)
The understanding of catalytic reactions at the atomic interface is vital; however, the characterization and mechanism studies of atomically dispersed catalysts remain challenging. Here, the authors demonstrate Cu–Sn surface alloys with isolated Sn atoms on a Cu host to achieve efficient CO2 to CO conversion.